Prevention of Child and Juvenile Delinquency: A Case Study of the "Doing Good with Our Heart" Volunteer Project of Communities around Wat Prayurawongsawas Woravihara - บุญช่วย สัณหกฤษณ์; ธิราภรณ์ จตุพร (Journal of Thai Ombudsman, 2019)
This article has been written based on criminological theory as a guiding framework for the study and described the phenomenon that has occurred in contemporary society. This was a study and analysis of the possibility of implementing the “Doing Good with Our Heart” volunteer project as a guideline to prevent deviation and delinquency of children and juveniles in communities around Wat Prayurawongsawas Woravihara. The results showed that from on site, the “Doing Good with Our Heart” volunteer project could actually divert the attention of children and juveniles to avoid doing delinquencies, was consistent with the right culture, and has been accepted in the right way. It is a relationship with friends who work together. It is a bond to integrate activities within the minds of children and juveniles. Additionally, the activities of the “Doing Good with Our Heart” volunteer project were in accordance with the King’s philosophy.